Music and words in the visual cortex: The impact of musical expertise. (January 2017) - Mongelli, Valeria; Dehaene, Stanislas; Vinckier, Fabien; Peretz, Isabelle; Bartolomeo, Paolo; Cohen, Laurent
Abstract: How does the human visual system accommodate expertise for two simultaneously acquired symbolic systems? We used fMRI to compare activations induced in the visual cortex by musical notation, written words and other classes of objects, in professional musicians and in musically naïve controls. First, irrespective of expertise, selective activations for music were posterior and lateral to activations for words in the left occipitotemporal cortex. This indicates that symbols characterized by different visual features engage distinct cortical areas. Second, musical expertise increased the volume of activations for music and led to an anterolateral displacement of word-related activations. In musicians, there was also a dramatic increase of the brain-scale networks connected to the music-selective visual areas. Those findings reveal that acquiring a double visual expertise involves an expansion of category-selective areas, the development of novel long-distance functional connectivity, and possibly some competition between categories for the colonization of cortical space.